2017
DOI: 10.1007/s12351-017-0305-x
|View full text |Cite
|
Sign up to set email alerts
|

On the optimal solution of budgeted influence maximization problem in social networks

Abstract: The budgeted influence maximization problem is a challenging stochastic optimization problem defined on social networks. In this problem, the objective is identifying influential individuals who can influence the maximum number of members within a limited budget. In this work an integer program that approximates the original problem is developed and solved by a sample average approximation (SAA) scheme. Experimental analyses indicate that SAA method provides better results than the greedy method without worsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…Recently, Wang and Yu [2020] studied the BIM Problem and proposed a solution methodology that gives an approximation ratio of 1 2 (1 − 1 e ). They further showed that this can be improved upto Güney [2019] proposed an integer programming-based approach to solve this problem under the IC Model of diffusion. Han et al [2014] proposed a couple of heuristics for this problem that carefully considers both cost effective nodes and influential nodes.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, Wang and Yu [2020] studied the BIM Problem and proposed a solution methodology that gives an approximation ratio of 1 2 (1 − 1 e ). They further showed that this can be improved upto Güney [2019] proposed an integer programming-based approach to solve this problem under the IC Model of diffusion. Han et al [2014] proposed a couple of heuristics for this problem that carefully considers both cost effective nodes and influential nodes.…”
Section: Related Workmentioning
confidence: 99%
“…erefore, researchers have proposed many improved models to improve the efficiency of influence maximization [13][14][15]. Banerjee et al [16] designed a new heuristic algorithm for the prefix elimination maximum influence tree (PMIA) model and proposed the LDAG algorithm of the LT model.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a variant of this problem has been introduced by Nguyen and Zheng Nguyen and Zheng [2013], where the users of the network are associated with a selection cost and the seed set selection is to be done within an allocated budget to maximize the influence in the network. There are a few solution methodologies of the problem such as directed acyclic graph (DAG)-based heuristics and (1− 1 √ e )-factor approximation algorithm by Nguyen and Zheng [2013], balanced seed selection heuristics by Han et al [2014], integer programming-based approach Güney [2017], community-based solution approach by Banerjee et al [2019a]. In all these studies it is implicitly assumed that irrespective of the context, influence probability between two users will be the same, i.e., there is a single influence probability associated with every edge.…”
Section: Introductionmentioning
confidence: 99%